2021
DOI: 10.3390/biomedicines9050515
|View full text |Cite
|
Sign up to set email alerts
|

HOXB7 Overexpression Leads Triple-Negative Breast Cancer Cells to a Less Aggressive Phenotype

Abstract: HOX genes appear to play a role in breast cancer progression in a molecular subtype-dependent way. The altered expression of HOXB7, for example, was reported to promote breast cancer progression in specific subtypes. Here we induced HOXB7 overexpression in MDA-MB-231 cells, a cellular model of the Triple-Negative breast cancer molecular subtype, and evaluated the phenotypic changes in cell viability, morphogenesis, migration, invasion, and colony formation. During the phenotypic characterization of the HOXB7-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…These data are in agreement with previous reports suggesting that CDH1 is a methylation-silenced gene in these cells [35]. We then investigate whether HOXB7 overexpression may have an impact on the methylation of E-cadherin in MDA-MB-468 cells, as reported recently for other triple-negative breast cancer cells [21]. To this end, we characterized the CDH1 methylation status in HOXB7-silenced cells and controls using bisulfite conversion followed by sequencing analyses.…”
Section: Impact Of Hoxb7-silencing In the Methylation Profile Of The E-cadherin Promoter In Triple-negative Breast Cancer Cellssupporting
confidence: 88%
See 4 more Smart Citations
“…These data are in agreement with previous reports suggesting that CDH1 is a methylation-silenced gene in these cells [35]. We then investigate whether HOXB7 overexpression may have an impact on the methylation of E-cadherin in MDA-MB-468 cells, as reported recently for other triple-negative breast cancer cells [21]. To this end, we characterized the CDH1 methylation status in HOXB7-silenced cells and controls using bisulfite conversion followed by sequencing analyses.…”
Section: Impact Of Hoxb7-silencing In the Methylation Profile Of The E-cadherin Promoter In Triple-negative Breast Cancer Cellssupporting
confidence: 88%
“…Our data showed that with the silencing of HOXB7 in MDA-MB-468 cells, the expression of CDH1 increased. Recent functional assays performed in MDA-MB-231 cells revealed enriched interactions between the HOXB7 protein and CDH1 [21]. Thus, we hypothesize that HOXB7 deregulation may affect CDH1 expression in multiple triple-negative BC cells.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations